Life an introduction to biology - Gaylard Simpson, G.; Beck, W.S. (New York (EUA), 1969)
Resumen (En)
Ilus; Resumenes por capítulo
Keywords: BIOLOGIA; EVOLUCION; CELULAS; REPRODUCCION; CROMOSOMAS; HERENCIA GENETICA; GENES; VARIACION GENETICA; BIODIVERSIDAD; PLANTAS; ANIMALES; POBLACION ANIMAL; POBLACION VEGETAL; POBLACION HUMANA; MEDIO AMBIENTE; BIOGEOGRAFIA